Increasing Elderly Knowledge Menopause and Physical Health Through Tera Exercise in Selokerto Village, Kebumen Regency - Kusumastuti, K; Rahmadhani, Wulan; Prabandari, Fitria (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Menopause is the permanent cessation of menstruation due to the failure of the ovarian follicles. Various problems arise in the menopausal process, can be in the form of hormonal deficits, social psychology and diseases in the elderly. One of the efforts that can be done is to increase knowledge and exercise Tera gymnastics. Tera Gymnastics is a physical and mental exercise, combining body movements with regular, harmonious, correct and continuous breathing techniques and rhythms. The methods used include preparation, implementation and evaluation. At the preparatory stage, it was carried out in coordination with the village head, village midwife, head of the puskesmas and health cadres of Selokerto Village. The service team also prepared rooms, tape recorders, gymnastics instructors, presentation media, and questionnaires. In the second stage, the implementation consisted of increasing knowledge about menopause by involving health workers from the Sempor 1 Health Center then doing tera gymnastics. The activity was attended by 20 senior citizens of Selokerto Village. The third stage is evaluation by conducting pre-test and post-test during the implementation of increasing knowledge of menopause using a questionnaire. The results of this community service, get an increase in knowledge of menopause. After being given education about menopausal problems, there was an increase in knowledge from the category of sufficient knowledge (78.9%) to the category of good knowledge (73.7%). In conclusion, it is necessary to activate the Posyandu for the elderly by holding tera gymnastics to improve the health of the elderly in the Selokerto village area, SemporDistrict, Kebumen Regency.